Kerugian Investor yang Diakibatkan Gagal Bayar Dana Investasi Reksa Dana oleh Manajer Investasi Menurut Peraturan di Bidang Pasar Modal - Laili Aristawati; Toto Tohir Suriatmadja; Frency Siska (UNISBA Press, 2022)
Abstract. The case of default investment funds through Mutual Fund instruments experienced by investors in the capital market by the Investment Manager for violating actions, has caused financial loss to investors. This study raises the issue of investor financial loss caused by failure to pay Mutual Fund investment funds by Investment Managers according to capital market regulations. This study uses a normative juridical method with descriptive analytical research specifications. The results of the study conclude that based on Law Number 8 of 1995 concerning the Capital Market, investors who experience loss of Mutual Fund investment funds resulting from the actions of Investment Managers who fail to pay investment funds on Mutual Fund instruments have the right to obtain compensation for any financial loss incurred. experienced by investors. But in fact, investors have not received a number of compensation from the Investment Manager. Responding to the investors' financial loss above, it is necessary to conduct this research as an effort to minimize the occurrence of violation by Investment Managers and reduce financial loss for Mutual Fund investors. Abstrak. Kasus gagal bayar dana investasi melalui instrumen Reksa Dana yang dialami oleh investor di pasar modal yang dilakukan oleh Manajer Investasi atas perbuatan yang melanggar, telah menimbulkan kerugian bagi investor. Penelitian ini mengangkat permasalahan mengenai kerugian investor yang diakibatkan gagal bayar dana investasi Reksa Dana oleh Manajer Investasi menurut peraturan di bidang pasar modal. Penelitian ini menggunakan metode yuridis normatif dengan spesifikasi penelitian deskriptif analitis. Hasil penelitian menyimpulkan bahwa berdasarkan Undang-Undang Nomor 8 Tahun 1995 tentang Pasar Modal, investor yang mengalami kerugian dana investasi Reksa Dana yang ditimbulkan dari perbuatan Manajer Investasi yang mengalami gagal bayar dana investasi pada instrumen Reksa Dana memiliki hak untuk mendapatkan ganti rugi atas segala kerugian yang dialami investor. Namun faktanya, investor belum mendapatkan sejumlah ganti rugi dari Manajer Investasi. Menyikapi kerugian investor diatas, maka perlu kiranya ada penelitian ini sebagai upaya meminimalisirkan terjadinya pelanggaran oleh Manajer Investasi dan menekan kerugian bagi investor Reksa Dana.